Modification and characterization of a standard LISN for effective EMI noise separation - Stahl, Jürgen; Kübrich, Daniel; Dürbaum, Thomas (International Conference on Electromagnetics in Advanced Applications (ICEAA 2010 - Offshore), 2010)
The compliance with standards calls for proper designed EMI filters. EMI typically comprises common mode (cm) and differential mode (dm) noise. A systematic optimization of EMI filters requires the knowledge of the contribution and distribution of these two noise sources. The paper discusses different methods that allow the independent measurement of cm and dm noise. One suitable method described in detail integrates the separation set-up into the Line Impedance Stabilization Network (LISN). However, a correct interpretation of the measured results requires a characterization of the unavoidable crosstalk of the complete set-up - i.e. the measured level at the dm output in case of pure cm excitation and vice versa. As shown in this paper, the implementation of a standard LISN introduces the highest amount of imperfections causing the undesired crosstalk. Thus, for the first time, this paper describes the characterization of the whole set-up including the LISN. ©2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.modifi